On "Imposed Interpretation" in Literary Criticism: The Issue of "French Theory". (2nd July 2016) - Camelin, Colette
Abstract: This paper is a response to what Professor Zhang Jiang of the Chinese Academy of Social Sciences (CASS) terms as "imposed interpretation." In his article "On Imposed Interpretation, " Professor Zhang sees imposed interpretation as a fundamental feature and basic defect of contemporary Western literary criticism. The author analyzes some of the interpretations, as criticized by Professor Zhang, imposed on some literary classics by feminist, eco-critical, psychoanalytical, structuralist and deconstructivist methods. She reviews the sources and the limitations of the so-called "French theory" in cultural studies courses in American universities before raising the critical practice she endorses: a synthesizing critical methodology that is based on the specificity of the text, uses multiple applicable theories in relation to the socio-temporal context in which the work was produced, while bearing in mind the author's intentions and the reader's active participation. Through rigorous textual analysis, literary criticism can identify some new perspectives offered by the text which enable construction of the meaning of the text and of life. This can highlight the functions of literary reading in enriching people's lives and enhancing the role of reality and man's spiritual realm.